Hilo. Book 3, The great big boom - Winick, Judd (Winick, Judd. Hilo, 2017)
Hilo and DJ, with the help of Polly, the magical warrior cat, travel through a mysterious portal and battle bad guys, face disgusting food, an angry mom, and powerful magic to save their friend Gina.